1992
DOI: 10.1007/s0054020060474
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, heart rate and catecholamine response during riberoptic nasotracheal intubation under general anesthesia

Abstract: Arterial blood pressure (ABP) and heart rate were recorded at one-minute intervals during several stages of intubation in the fiberscope group and the laryngoscope group, to determine if fiberoptic nasotracheal intubation would result in fewer hemodynamic and catecholamine responses than when intubation was performed with a Macintosh laryngoscope. Blood samples were also taken to measure plasma catecholamine concentration immediately after intubation with the fiberscope. The mean ABP in the laryngoscope group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Tsubaki et al . [2] found that following inhalational induction with 2% enflurane and 50% nitrous oxide, fibreoptic nasotracheal intubation resulted in less tachycardiac response and a similar pressor response compared with laryngoscopic nasotracheal intubation. The plasma concentrations of epinephrine and norepinephrine did not significantly change in the fibreoptic nasotracheal intubation group, but increased significantly in the laryngoscopic nasotracheal intubation group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsubaki et al . [2] found that following inhalational induction with 2% enflurane and 50% nitrous oxide, fibreoptic nasotracheal intubation resulted in less tachycardiac response and a similar pressor response compared with laryngoscopic nasotracheal intubation. The plasma concentrations of epinephrine and norepinephrine did not significantly change in the fibreoptic nasotracheal intubation group, but increased significantly in the laryngoscopic nasotracheal intubation group.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheal intubation which is accomplished with a fibreoptic bronchoscope is thought to attenuate the circulatory responses to intubation as stimulation of oropharyngeal structures may be avoided. However, previous studies have provided inconsistent findings [1–4]. Smith et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically performed in the office or bedside setting, TNFE provides the observer with a superior view of laryngeal function and pathology compared to indirect endoscopy with the laryngeal mirror. TNFE is practiced by physicians and allied health‐care providers from multiple disciplines, including anesthesiology, pediatric medicine, pulmonology, radiation oncology, and speech‐language pathology 2, 3. With the advent of distal chip technology, the improved resolution of vocal fold anatomy and pathophysiology has spurred the practice of office‐based interventional procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Since TNFE has become common practice, few data have been collected on its safety outside of its use in nasotracheal intubation 2, 6. On the whole, this has led to the blind acceptance of TNFE as safe with minimal adverse side effects.…”
Section: Introductionmentioning
confidence: 99%